Can communal systems work? The effects of communal water provision on child health in Peru. (April 2021) - Calzada, Joan; Iranzo, Susana
Highlights: We assess the impact of communal versus public water provision on child health in Peru. Identification strategy based on the discontinuity in the type of provision across district sub-units. Communal organizations result in better health outcomes in historical Inca settlements. Long-standing effects of the Minka tradition of collective work. Social norms and traditions are important for the success of communal projects. Abstract: Communal water organizations are widespread in many areas of developing countries, where local governments lack the resources to offer a minimum quality water service. However, these organizations have their own resource limitations and they additionally face the well-known problems associated with collective action. It is therefore unclear how effectively they can provide safe water, and the evidence available thus far is mixed. This paper analyzes the communal water organizations in Peru known as Juntas Administrativas de Servicios de Saneamiento (JASS). Using detailed household survey data, we empirically assess the differential impact of the JASS vis-à-vis public systems on two water-related child health outcomes: diarrhea and low birth weight. Our identification strategy exploits the legislative changes introduced in the 2000s and the arbitrary cut-off to classify the administrative sub-units of Peruvian municipalities (districts) in order to achieve exogenous variation in the type of water provision. We find that child diarrhea and low birth weight are significantly lower for households served by JASS in the districts located in the first Inca settlements where the pre-Columbian tradition of communal work, called Minka, has survived over centuries. We also show that in those districts the JASS have better governance (existence of their own rules, higher participation and accountability and a greater ability to obtain external support). These findings confirm the hypothesis that social capital and traditions foster cooperation among community members and are in line with recent works showing the importance of historically developed institutions in building social capital. More generally, our results suggest that communal organizations are not a one-fits-all solution, but rather their success depends crucially on the existence of mechanisms for overcoming the problems associated with collective action and the active involvement of the community.